2021
DOI: 10.1093/nar/gkab050
|View full text |Cite
|
Sign up to set email alerts
|

siRNAs containing 2′-fluorinated Northern-methanocarbacyclic (2′-F-NMC) nucleotides: in vitro and in vivo RNAi activity and inability of mitochondrial polymerases to incorporate 2′-F-NMC NTPs

Abstract: We recently reported the synthesis of 2′-fluorinated Northern-methanocarbacyclic (2′-F-NMC) nucleotides, which are based on a bicyclo[3.1.0]hexane scaffold. Here, we analyzed RNAi-mediated gene silencing activity in cell culture and demonstrated that a single incorporation of 2′-F-NMC within the guide or passenger strand of the tri-N-acetylgalactosamine-conjugated siRNA targeting mouse Ttr was generally well tolerated. Exceptions were incorporation of 2′-F-NMC into the guide strand at positions 1 and 2, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 78 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…A possible explanation is that the functions of nucleotides 6 and 7 may slightly differ according to the siRNA sequence. As for other chemical modifications, it was reported that altritol nucleic acids and 2′-fluorinated Northern-methanocarbacyclic (2′-F-NMC) modifications at position 7 are also best accommodated and tolerated with the highest performance for the reduction of target gene expression. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…A possible explanation is that the functions of nucleotides 6 and 7 may slightly differ according to the siRNA sequence. As for other chemical modifications, it was reported that altritol nucleic acids and 2′-fluorinated Northern-methanocarbacyclic (2′-F-NMC) modifications at position 7 are also best accommodated and tolerated with the highest performance for the reduction of target gene expression. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…Our laboratory has been interested in studying noncanonical nucleic acid modifications, and we recently reported the synthesis of small interfering RNAs (siRNAs) containing 2′-fluorinated northern -methanocarbacyclic (2′-F-NMC) nucleotides (Figure A). , The 2′-F-NMC scaffold preorganizes the carbocyclic sugar into a pseudo-boat C2′- exo (north) conformation . 2′-F-NMC was generally well tolerated in both the guide and passenger strands of siRNAs with some exceptions, such as positions 1 and 2 on the guide strand. , This prompted us to evaluate the carbocyclic nucleotides, the parent compounds of the NMC scaffold. We have also studied how modifications with low thermal binding affinity such as ( S )-glycol nucleic acid (( S )-GNA), which is also devoid of the 4′-oxygen, mitigates off-target effects of siRNAs …”
mentioning
confidence: 99%
“…Native NTPs (rCTP, rUTP, dCTP, and dTTP) are efficiently incorporated by the mitochondrial DNA and RNA polymerases POLG and POLRMT, respectively. , Although 2′-F monomers are incorporated at high concentrations by POLRMT, the 2′-F/Me-modified nucleotide analogues are not substrates for either mitochondrial polymerase. The inability of POLG to incorporate 2′-F/Me-modified residues can be readily explained by an unfavorable interaction between the 2′-Me moiety and the “gatekeeper” residue Tyr-951 at the active site. When a 2′-F/Me CMP from a refined duplex structure (C3′- endo pucker) is superimposed on the incoming dCTP in the crystal structure of the ternary POLG complex (PDB ID 4ZTZ), the gem -hetero-substituted methyl group points directly into the ring of that tyrosine thereby creating a clash (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Native NTPs (rCTP, rUTP, dCTP, and dTTP) are efficiently incorporated by the mitochondrial DNA and RNA polymerases POLG and POLRMT, respectively. 40,75 Although 2′-F monomers are incorporated at high concentrations by POLRMT, the 2′-F/Me-modified nucleotide analogues are not substrates for either mitochondrial polymerase. 15−17 The inability of POLG to incorporate 2′-F/Memodified residues can be readily explained by an unfavorable interaction between the 2′-Me moiety and the "gatekeeper" residue Tyr-951 at the active site.…”
Section: Structural Rationalization For Poor Incorporation Of 2′f/me ...mentioning
confidence: 99%